2014
DOI: 10.1186/1471-2407-14-728
|View full text |Cite
|
Sign up to set email alerts
|

Survival in overweight patients with advanced pancreatic carcinoma: a multicentre cohort study

Abstract: BackgroundObesity is a risk factor for developing pancreatic cancer. We investigated the impact of obesity on survival in patients diagnosed with locally advanced or metastatic pancreatic cancer.MethodsIn a multicentre, retrospective study, we included all patients with advanced or metastatic pancreatic cancer treated at four Swiss hospitals between 1994 and 2004. We categorized patients into four body mass index (BMI) groups (<18.5, 18.5 – 25, ≥ 25 – 29, ≥30 kg/m2) and used multivariable Cox regression to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Other studies have shown an association of peripheral MDSCs with age [29] and obesity [30, 31], risk factors associated with poorer outcomes in pancreatic cancer patients [32]. We were unable to correlate the frequency of MDSC in the spleen with these clinical characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have shown an association of peripheral MDSCs with age [29] and obesity [30, 31], risk factors associated with poorer outcomes in pancreatic cancer patients [32]. We were unable to correlate the frequency of MDSC in the spleen with these clinical characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…However, the data are inconsistent for breast cancer (11) and pancreatic cancer (12, 13), and no associations have been observed in ovarian cancer (14), colorectal cancer (15), lymphoma (14), pancreatic cancer, or esophageal cancer (16). In contrast, higher BMI at diagnosis has been associated with better prognosis in acute myeloid leukemia (17), multiple myeloma (18), head and neck cancers (19), and among women with non-Hodgkins lymphoma (9).…”
Section: Introductionmentioning
confidence: 99%
“…Higher BMI has been linked to shorter survival in some cancer types, such as colorectal and pancreatic cancers (Kasenda et al, 2014;Vrieling & Kampman, 2010). In contrast, other studies have reported lower mortality among overweight or mildly obese patients with colorectal cancer (CRC) (Schlesinger et al, 2014), clear cell renal cell carcinoma (RCC) (Hakimi et al, 2013) and patients with advanced gastrointestinal or lung cancer (Martin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%